The Weight of Remembering: Cultural Trauma and Identity Formation in Toni Morrison's Song of Solomon and Ta-Nehisi Coates's the Water Dancer - YILDIZ, DENİZ (İstanbul Kültür Üniversitesi, 2025)
This thesis examines the cultural trauma of slavery and its destructive impact on the formation of African American identities in the works of Toni Morrison's Song of Solomon and Ta-Nehisi Coates's The Water Dancer. Since the two novels are set in distinct historical periods (the Civil Rights Movement and the late antebellum America), they provide the brutal realities of slavery both as a lived experience and as an inherited trauma. They also reframe the existing historical narratives by putting forth a counter history against historical erasure. In doing so, each novel is enriched with African American cultural myths and motives incorporated with magical realism. Through this, both novels put emphasis on memory, remembering of one's heritage, and the necessity of communal engagement for the betterment of the self. In exploring these intersecting themes, this study draws on the theoretical frameworks of trauma theory, memory studies, postcolonialism and postmodernism.
Keywords: African American Literature; The Legacy of Slavery; Cultural Trauma; Cultural Memory; African American Identity; Postcolonialism; Postmodernism; Magical Realism